The tyrosine kinase inhibitor lenvatinib is oxidized by rat cytochromes P450 and affects their expression in rat liver - Indra, Radek; Jelínková, Sandra; Kollárová, Katarína; Zahumenská, Petra; Dvořák, Josef; Dušková, Šárka; Dračínská, Helena (Acta pharmaceutica (Zagreb, Croatia), 2024)
Lenvatinib is an orally effective tyrosine kinase inhibitor used to treat several types of tumors, including progressive, radioiodine-refractory differentiated thyroid cancer and advanced renal cell carcinoma. Although this drug is increasingly used in therapy, its metabolism and effects on the organism are still not described in detail. Using the rat as an experimental animal model, this study aimed to investigate the metabolism of lenvatinib by rat microsomal enzymes and cytochrome P450 (CYPs) enzymes recombinantly expressed in SupersomesTM in vitro and to assess the effect of lenvatinib on rat CYP expression in vivo. Two metabolites, O-desmethyl lenvatinib, and lenvatinib N-oxide, were produced by rat CYPs in vitro. CYP2A1 and 2C12 were found to be the most effective in forming O-desmethyl lenvatinib, while CYP3A2 was found to primarily form lenvatinib N-oxide. The administration of lenvatinib to rats caused changes in the expression of mRNA and protein, as well as the activity of various CYPs, particularly in an increase in CYP1A1. Thus, the administration of lenvatinib to rats has an impact on the level of CYPs.
Keywords: Liver; Phenylurea Compounds; messenger RNA; Microsomes, Liver; Rats; játra; Quinolines; systém (enzymů) cytochromů P-450; Protein Kinase Inhibitors; potkani Sprague-Dawley; mužské pohlaví; protein expression; tyrosine kinase inhibitor; Oxidation-Reduction; Cytochrome P-450 Enzyme System; cytochrome P450; krysa rodu Rattus; fenylmočovinové sloučeniny; inhibitory tyrosinkinasy; RNA, Messenger; zvířata; Tyrosine Kinase Inhibitors; Rats, Sprague-Dawley; jaterní mikrozomy; oxidace-redukce; inhibitory proteinkinas; lenvatinib; chinoliny; Male; Animals